First trimester interleukin‐6 levels help to predict adverse pregnancy outcomes in both thyroid autoantibody positive and negative patients. Issue 11 (26th August 2015) - Oztas, Efser; Erkenekli, Kudret; Ozler, Sibel; Aktas, Aynur; Buyukkagnıcı, Umran; Uygur, Dilek; Danisman, Nuri
Abstract: Aim: The aim of the present study is to compare pregnancy outcomes among patients with and without thyroid antibodies and/or subclinical hypothyroidism and investigate whether there is an association between first trimester maternal plasma interleukin‐6 (IL‐6) levels and adverse pregnancy outcomes. Methods: A case‐control study was carried out including 83 pregnant women (40 thyroid antibody positive and 43 healthy controls). The predictive value of first trimester maternal plasma IL‐6 levels on adverse pregnancy outcomes were investigated. The optimal cut‐off points of IL‐6 for determining maternal and fetal outcomes were evaluated by receiver operating characteristic analyses. Results: Compared with the control, median IL‐6 levels were significantly higher in thyroid antibody positive pregnancies (median 1.58 vs 1.63 pg/mL; P = 0.047). IL‐6 levels were found to be significantly higher in women who had suffered a miscarriage ( P = 0.002), preterm delivery ( P < 0.001), intrauterine growth restriction ( P = 0.047), preterm premature rupture of membranes ( P = 0.043) and overall prenatal complications ( P < 0.001). A statistically significant negative correlation between gestational week at birth and IL‐6 levels was also determined among all participants involved in the study (r = ‐0.385, P < 0.001). Conclusion: IL‐6 levels are significantly increased in thyroid antibody positive patients and predictive for future adverse outcomes, irrespective of thyroid autoimmunity. Increased first trimester IL‐6 levels independently predict adverse pregnancy outcomes, regardless of subclinical hypothyroidism.